ВЛИЯНИЕ ВЫСОКОЙ ТЕМПЕРАТУРЫ ОКРУЖАЮЩЕЙ СРЕДЫ НА АДАПТАЦИОННЫЕ ВОЗМОЖНОСТИ СЕРДЕЧНО-СОСУДИСТОЙ СИСТЕМЫ К ФИЗИЧЕСКОЙ НАГРУЗКЕ И СПОРТИВНУЮ РАБОТОСПОСОБНОСТЬ - Хужабеков, М.А. (SCIENCE and SOCIETY, 2020)
The article presents data on the adaptive capacity of the cardiovascular system of athletes to perform physical activities in a high temperature environment in a hot climate. Recently, sports events are widely held in Central Asia, where one of the environmental factors is high air temperature and solar insolation, which can negatively affect the functional state of the body in the summer.
Keywords: adaptation; physical activity; insolation; climate; heart rate; thermoregulation